Vulnerable narcissism as beneficial factor for the therapeutic alliance in borderline personality disorder. (22nd February 2021) - Busmann, Mareike; Meyer, Andrea H.; Wrege, Johannes; Lang, Undine E.; Gaab, Jens; Walter, Marc; Euler, Sebastian
Abstract: Evidence suggests that narcissism and borderline personality disorder are associated with each other. This naturalistic study investigated the predictive value of grandiose and vulnerable narcissism on the development of the therapeutic alliance in short‐term psychodynamic treatment across 12 weeks. The sample consisted of 99 patients with borderline personality disorder. Narcissism was assessed with the Pathological Narcissism Inventory at treatment onset. The therapeutic alliance was rated with the Scale to Assess Therapeutic Relationships by both patient and therapist at four time points during treatment. Results showed a significant predictive value of vulnerable narcissism on the therapeutic alliance, revealing a more beneficial progression for patients with higher vulnerable narcissism. Grandiose narcissism had no predictive value on the therapeutic alliance. The study strengthens the clinical utility of the concept of vulnerable narcissism towards the evaluation of treatment processes in borderline personality disorder.